Pandemic-induced reductions on swim training volume and performance in collegiate swimmers - Martinez Perez, G.; VanSumeren, M.; Brown, M.; Hew-Butler, T. (Preprints, 2018)
Abstract: The COVID-19 pandemic caused significant training disruptions during the 2020-21 season due to lockdowns, quarantines, and strict adherence to pandemic protocols. The main purpose of this study was to determine how pandemic training restrictions affected training volume and performance in one collegiate swim team. Cumulative training volume data, across a 28-week season, were compared between a pandemic (2020-2021) versus non-pandemic (2019-2020) season. Swimmers were categorized into three groups (Sprinters, Mid-Distance, and Long-Distance) based on training group. Performance times in 25 swimmers who competed in Regional Championships, during both the non-pandemic and pandemic year, were compared via 1-way ANOVA. 26 male and 22 female swimmers commenced the 2020-21 (pandemic) season, with 23% of swimmers voluntarily opting out. Three COVID-19 cases were confirmed (2%) by the medical staff with no long-term effects. Significant reductions in average swim volume were verified in Sprinters (32,867±10,135vs.14,800±7,995yards;p<0.001),Mid-Distance (26,457±10,692vs.17,054±9.923yards;p<0.001), and Long-Distance (37,600±14,430 vs.22,254±14,418yards;p<0.001) swimmers (non-pandemic vs. pandemic season, respectively). In the Regional performance analyses, the Sprinters swam faster (n=8;-0.5±0.6secs), while Mid-Distance (n=10;0.17±2.1secs) and Long-Distance (n=7;6.0±4.9secs) swimmers swam slower (F=11.76;p=0.0003;r2=0.52). Thus, the pandemic caused significant reductions in swim training volume, with Sprinters performing better and Long-Distance swimmers performing worse at Regional Championships